2017
DOI: 10.1038/s41598-017-05309-w
|View full text |Cite
|
Sign up to set email alerts
|

An intragenic mutagenesis strategy in Physcomitrella patens to preserve intron splicing

Abstract: Gene targeting is a powerful reverse genetics technique for site-specific genome modification. Intrinsic homologous recombination in the moss Physcomitrella patens permits highly effective gene targeting, a characteristic that makes this organism a valuable model for functional genetics. Functional characterization of domains located within a multi-domain protein depends on the ability to generate mutants harboring genetic modifications at internal gene positions while maintaining the reading-frames of the fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…Upon successive genotyping for the loss of the WT locus using the primer pair P‐1/P‐2, the presence of 5′ vector insertion with the primer pair P‐3/P‐5 and the presence of the vector 3′ insertion with the primer pair P‐4/P‐6 and finally the detection of a single copy of the insert using the primer pair P‐3/P‐4, three transformants were found to contain a single insertion at the locus. The observed Δdek1 phenotype indicated that the construct insertion generated a null phenotype potentially caused by the mis‐splicing of the modified intron that contained the resistance cassette, a phenomenon observed previously in Physcomitrella (Demko et al , ; Johansen et al , ; Ako et al , ). To remove the resistance cassette, we subsequently transiently expressed the Cre recombinase (Trouiller et al , ) in protoplasts of the primary transformant dek1‐pArrowf1‐1 containing a single insert at the locus.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Upon successive genotyping for the loss of the WT locus using the primer pair P‐1/P‐2, the presence of 5′ vector insertion with the primer pair P‐3/P‐5 and the presence of the vector 3′ insertion with the primer pair P‐4/P‐6 and finally the detection of a single copy of the insert using the primer pair P‐3/P‐4, three transformants were found to contain a single insertion at the locus. The observed Δdek1 phenotype indicated that the construct insertion generated a null phenotype potentially caused by the mis‐splicing of the modified intron that contained the resistance cassette, a phenomenon observed previously in Physcomitrella (Demko et al , ; Johansen et al , ; Ako et al , ). To remove the resistance cassette, we subsequently transiently expressed the Cre recombinase (Trouiller et al , ) in protoplasts of the primary transformant dek1‐pArrowf1‐1 containing a single insert at the locus.…”
Section: Resultssupporting
confidence: 58%
“…Insertion of a fluorescent tag within a native locus can generate unwanted phenotypes either due to the vector insertion or from the tag itself (Ako et al , ). In order to minimize this risk, we adopted the two steps strategy used previously in partial gene deletion in P. patens (Demko et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…How exactly the multi-spanning transmembrane domain and Linker domain contribute to the DEK1 function, and especifically to the calpain regulation, remains largely unknown. Important data suggesting a regulatory role of the MEM and Linker domains have been provided by targeted mutagenesis of P. patens DEK1 ( Demko et al., 2014 ; Johansen et al., 2016 ; Ako et al., 2017 ) and electrophysiology studies of plants with modified DEK1 accumulation in A. thaliana ( Tran et al., 2017 ).…”
Section: The Only Membrane-anchored Calpain With Known Biological Rol...mentioning
confidence: 99%
“…The protein model was generated using IBS. 11 these specific loci could yield improper gene splicing 21 and thus to the absence of functional DEK1. Alternatively, the presence of a tag at these specific positions could impede totally DEK1 protein synthesis or its further function and lead to the Δdek1 phenotype.…”
mentioning
confidence: 99%